Evaluación económica de tecnologías forrajeras en Colombia: Avena Altoandina and Arachis pintoi CIAT 22260 - Enciso, Karen; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2020)
This document aims to assess the financial viability of two new forage options released in Colombia as a result of different evaluation and selection processes conducted by AGROSAVIA and its partners. The following varieties were evaluated from an economic perspective: (i) Avena Altoandina for intensified dairy production in the high-altitude tropics of Colombia; and ii) Arachis pintoi CIAT 22260 for a double-purpose production system in the foothills of the Colombian Orinoquía region. The methodology is based on a discounted free cash flow model, the estimation of financial feasibility indicators, and an analysis that is based on Monte Carlo simulation, to consider the risk level of critical variables of the model. In the case of Arachis, we included potential impacts of climate change in the model. The results provide a valuable information source for livestock producers, extensionists, policy and other actors for making informed decisions on whether or not invest in these new technologies.